Treatment and outcomes of multidrug‐resistant tuberculosis in Auckland, 1995–2018. Issue 8 (31st May 2022) - Cutfield, Tim; Mowlem, Lydia; Paynter, Jennifer; Christmas, Timothy; Harrison, Adrian; Lewis, Christopher; Newton, Sandra; Nisbet, Mitzi
Abstract: Background: New Zealand has a low burden of tuberculosis; however, multidrug‐resistant tuberculosis (MDR‐TB) still represents a challenge for clinicians. This is the first description of clinical aspects of MDR‐TB in New Zealand. Aims: To evaluate the treatment and outcomes of patients with MDR‐TB disease in Auckland. Secondary aims were to review the incidence and clinical characteristics of MDR‐TB disease. Methods: Clinical data were obtained for patients treated for MDR‐TB at Auckland District Health Board (ADHB). Results: There were 60 patients nationally with MDR‐TB between 1989 and 2018; 41 (69%) of 60 patients received care at ADHB. Pulmonary infection was present in 36 (88%) of 41 patients, with 19 (46%) of 41 patients with smear‐positive sputum (smear 1–2+ in 6/41, 15%; smear 3–4+ in 13/41, 32%). The median duration of treatment was 22 months (range 7.5–26) for 18 (44%) of 41 patients who completed MDR‐TB treatment by August 2018. The median duration of amikacin treatment was 6 months (range 2–12) for the 23 (61%) of 38 patients in whom these data were available. All 38 patients who received treatment for MDR‐TB experienced adverse effects, most commonly gastrointestinal (66%), neurological (50%), ototoxicity (47%) and psychiatric (37%). Complications of intravenous access were experienced by 10 (27%) of 37 patients. Of the 19 (46%) of 41 patients who completed treatment, 18 (95%) achieved cure. There was one case who had recurrence because of inadequate treatment, and one case who had spontaneous resolution without treatment. Seventeen (41%) patients left Auckland prior to completion of treatment, mostly to return to their country of origin (15/17, 88%). Conclusion: MDR‐TB is uncommon in New Zealand. Treatment is frequently associated with adverse events; however, rates of cure for people completing treatment in New Zealand are high.